A retrospective cohort study of body mass index and survival in HIV infected patients with and without TB co-infection - Kogieleum Naidoo; Nonhlanhla Yende-Zuma; Stanton Augustine (BMC, 2018)
Abstract Background High early morbidity and mortality following antiretroviral therapy (ART) initiation has been a distinguishing feature of ART programmes in resource limited settings (RLS) compared to high-income countries. This study assessed how well body mass index (BMI: kg/m2) correlated with survival among HIV infected patients with and without TB co-infection. Methods We retrospectively evaluated clinical data from 1000 HIV infected patients, among whom 389 were also co-infected with TB, between January 2008 and December 2010, in KwaZulu-Natal, South Africa. Results Among 948 patients eligible for analysis, 15.7% (149/948) were underweight (< 18.50), 55.9% (530/948) had normal BMI (≥18.50-24.90), 18.7% (177/948) were overweight (25.00-29.00) and 9.7% (92/948) were obese (≥30.00). Irrespective of TB status, underweight patients, had significantly higher risk of death compared to those with normal BMI at baseline (aHR = 2.9; 95% CI: 1.5-5.7; P = 0.002). Conclusions Irrespective of TB co-infection, low BMI correlated with mortality in HIV infected patients. Trial registration UKZN Biomedical Research Ethics Committee Reference number E 248/05, 23 September 2005.